Enriching folksonomy for online videos. (15th May 2019) - Sakaji, Hiroki; Kohana, Masaki; Kobayashi, Akio; Sakai, Hiroyuki
We propose a method that enriches folksonomy by using user comments on online videos. Folksonomy is a process in which users tag videos so that they can be searched for easily. On some videos, users can post tags and comments. A tag corresponds to folksonomy. One such online sharing website is Nico Nico Douga; however, users cannot post more than 12 tags on a video. Therefore, there are some important tags that could be posted but are sometimes not. We present a method for acquiring some of these missing tags by choosing new tags that score well in a scoring method developed by us. The method is based on information theory and a novel algorithm for estimating new tags by using distributed databases constructed by us.